Pengaruh Good Corporate Governance, Konservatisme Akuntansi dan Ukuran Perusahaan terhadap Manajemen Laba yang Terdaftar di Bursa Efek Indonesia - Dwi Utami, Diah yeni; Nugraeni (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This research aims to examine the influence on Good Corporate Governance, Accounting Conservatim and the Size of Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange. The population in this research os the Manufacturing Industry in the Consumer Goods Sector which is listed on the Indonesia Stock Exchange from 2021 to 2022. The data used in this research is secondary data in thefrom of financial reports on Manufacturing Companies in the Consumer Goods Industry Sector which are listed on the Indonesia Stock Exchange. The data collection method in this reseach uses purposive sampling which analyzes 66 compnies listed on the Indonesia Stock Exchange and in this reseach uses multiple linear regression analyzes testing, where previously classific assumptions were tested first. Based on the research result. Good Corporate Governance and Company Size have no effect on earnings management. Accounting Conservatism has an effect on suppressing opportunistic actions on the part of managers on the part of company. So the higher the conservatism in a company, the lower the level of earnings management in that company. This research does not all cover earnings management in Manufacturing Companies in the Consumer Goods Sector, almost 22% includs measurement of Good Corporate Governance, Accounting Conservatism, and Company Size only and the rest is not explained in this research. In further research, it can be further developed by using the Good Corporate Governance scoring index to make it better and it is hoped that share ownership and the Board of Directors will be announced so that when taking samples, the results will be better.